PENGARUH BRAND IMAGE DAN BRAND ATTITUDE TERHADAP BRAND EQUITY KOSMETIK MEREK ORIFLAME PADA PEGAWAI SMA NEGERI 2 MUARA BADAK - BAHRI, KASMA; Wijayanti, Silvana Kardinar (I-Con Media, 2021)
The purpose of this study was to determine the influence of brand image and brand attitude simultanously and partially on brand equity of Oriflame Cosmetics. The samples in this study were 32 people consisting of employees at SMA Negeri 2, Muara Badak. The analytical tool used to analyze the data was multiple regression and hypotheses of this study tested using the F test and t test. The results of this study revealed that simultanously these two variables, namely band image and brand attitude have a significant effect on brand equity. Partially, brand image and brand attitude also have a significant effect on brand equity. Between these two variables the most influencing is brand attitude.